The Influence of Intellectual Capital, Innovation and Knowledge Management on Firm Performance - Anthonius S. Hutabarat; Hadita (International Journal of Science and Society, 2021)
This study aims to determine the effect of Intellectual Capital, Innovation, and Knowledge Management on firm performance. This research uses quantitative research with a descriptive analysis approach. The data used are primary and secondary. The population in this study are all MSME companies engaged in the fashion sector. At the same time, the samples in this study were 10 MSME Fashion companies in Jakarta, which were selected by random sampling method. The data collection method used in this research is field research in observation, interviews and questionnaires, and library research. The data analysis method used to determine the independent variable on the dependent variable used multiple linear regression formula using SPSS Version 20.0. A data analysis method is a tool used in solving problems. In addition, the analysis of research data using Validity Test, Reliability Test, Multiple Linear Regression Test and Hypothesis Testing. Based on the results of data analysis, it can be concluded that: 1) Intellectual Capital and Knowledge Management have a positive and significant effect on the performance of MSME Fashion companies in Jakarta, and 2) Innovation does not have a positive effect on the performance of MSME Fashion companies in Jakarta.